Corporate Social Responsibility and Organizational Psychology: An Integrative Review - Glavas, Ante (Frontiers in Psychology, 2016)
The author reviews the corporate social responsibility (CSR) literature that includes the individual level of analysis (referred to as micro CSR in the article) based on 166 articles, book chapters, and books. A framework is provided that integrates organizational psychology and CSR, with the purpose of highlighting synergies in order to advance scholarship and practice in both fields. The review is structured so that first, a brief overview is provided. Second, the literatures on organizational psychology and CSR are integrated. Third, gaps are outlined illuminating opportunities for future research. Finally, a research agenda is put forward that goes beyond addressing gaps and focuses on how organizational psychology and CSR can be partners in helping move both fields forward—specifically, through a humanistic research agenda rooted in positive psychology.